Refrigerador de bebidas de alto rendimento - Seelent, Jonas Josiel (2011)
In Brazil, it is customary in fellowship with friends and family to drink cold beer, preferably close to its solidification temperature, 0°C. Building a device capable of obtaining this temperature for a lot of beers and soon was the main goal of this work. The refrigerator is composed of condensing unit HEATCRAFT ®, model 075L6 FLEXK composed of a ¾ HP compressor cooling capacity of 596 kcal / h at an evaporating temperature of -25 ° C. The evaporator is the DELTA FRIO® model DFLD 4219 air circulation forced by a micro fan 1/10 hp. Will use a thermostatic expansion valve model Danfoss TS2. The refrigerant used is the R404A. O enclosure is built of steel plates bent, riveted and welded and heat insulation made of rigid polyurethane foam with 50 mm thick. The cabinet will be able to condition while 48 bottles of beer with a capacity of 600 ml. The port is done using stainless steel plate, painted in color metallic lead. The cost of acquisition and manufacture of the refrigerator is R$ 2743, 26. The time taken to freeze the 48 bottles of beer 28 ° C to -0 ° C was 1 hour and twenty minutes and energy consumption was 0.92 kW/h. In real this means R$ 0.42 per hour with the equipment in mode “fast cold” in which the compressor is active during the period required.